Internspoon Sdn Bhd (Internspoon) - Mohd Fikri Lai, Abdul Aziz Lai; Yahya, Ahmad Fareez (UiTM Newshub, 2022)
A signing ceremony of Memorandum of Understanding (MoU)between Universiti Teknologi MARA (UiTM) and Internspoon Sdn Bhd (Internspoon) was held atCommonGround Bangsar South, Kuala Lumpur, today.